Secondary Spontaneous Pneumothorax in Patients with Silicosis - Bairwa, Momkesh; Sharma, Ambika; Luniwal, Meengandha (Journal of the Association of Physicians of India, 2023)
: Patients with silicosis are at increased risk of pneumothorax. However, the true incidence of pneumothorax in these patients is yet unknown. Our objective was to study the proportion of secondary spontaneous pneumothorax (SSP) in patients with silicosis who present with acute respiratory deterioration. We also analyzed the risk factors, clinical course, actual management, and treatment outcomes of pneumothorax in patients with silicosis. : It was a hospital-based descriptive cross-sectional study. A total of hundred silicosis patients presenting with any acute worsening respiratory symptoms (dyspnea, cough, and chest pain) warranting admission were enrolled. A detailed history, clinical examination, and radiological investigations were done in all cases. : A total of 100 patients were included in this study. The mean age of subjects was 51.6 years. Breathlessness was the most common presenting symptom followed by chest pain. A total of 43 (43%) patients had pneumothorax at presentation. Right-sided pneumothorax was seen in 26 (26%) cases, left-sided in 11 (11%) cases, and six patients (6%) had bilateral pneumothorax. No significant correlation of smoking with pneumothorax was observed in the present study. Around 42% of patients had pulmonary tuberculosis which was microbiologically confirmed. : The present study emphasizes that all patients of silicosis who present with acute worsening shortness of breath and or chest pain need to be evaluated for pneumothorax. : Bairwa M, Sharma A, Luniwal M. Secondary Spontaneous Pneumothorax in Patients with Silicosis. J Assoc Physicians India 2023;71(10):64-66.